Social isolation and loneliness among Chinese older adults: Examining aging attitudes as mediators and moderators - Sun, Juanjuan; Jiang, Weikang; Li, Haohao (Frontiers in Psychology, 2022)
Due to labor migration and social changes, the Chinese elderly are facing significant social isolation, along with changes in aging attitudes. However, whether social isolation affects loneliness among the Chinese elderly and whether this relationship is moderated and mediated by aging attitudes is unclear. This empirical study aimed to respond to the above questions in the Chinese context, Based on the data from the 2014 China Longitudinal Aging Social Survey (N = 6,645), the results showed that social isolation is a positive predictor of loneliness; aging attitudes mediate the relationship between social isolation and loneliness. Social isolation affects the loneliness of the elderly partially by weakening positive aging attitudes and strengthening negative aging attitudes; aging attitudes moderate the effect of social isolation on loneliness. For those older adults with higher positive aging attitudes, social isolation has a much smaller effect on loneliness. While for those older adults with higher negative aging attitudes, social isolation has a more substantial effect on their feelings of loneliness. Our results indicate that less social isolation is an effective way to relieve loneliness, and maintaining higher positive aging attitudes and lower negative aging attitudes, is important for the Chinese elderly to prevent loneliness when facing social isolation.